It is: 3x2+6x-11 = 0
From what i understand the equation is like this; (3 * 2 ) + 6x + 24 = 0 6 + 6x +24 = 0 6x = - 24 - 6 6x = - 30 x = - 5
6x+5=3x+5 5=9x+5 x=0
x^2 + 3x + 7 = 6x + 18 x^2 - 3x - 11 = 0
2x2+6x-8 = 72 2x2+6x-8-72 = 0 2x2+6x-80 = 0 (2x-10)(x+8) = 0
It is: 3x2+6x-11 = 0
From what i understand the equation is like this; (3 * 2 ) + 6x + 24 = 0 6 + 6x +24 = 0 6x = - 24 - 6 6x = - 30 x = - 5
x2 + 6x + 8 = 0 Solve for x.X = -2 or X = -4
7x + 2 = 6x + 2 if and only x = 0.
x+15+(-15)=6x+(15+(-15)=6x+(15-15)=6x+(0)=6x+0=6Add/subtract 0 from both sides,x=6
6x+5=3x+5 5=9x+5 x=0
x^2 + 3x + 7 = 6x + 18 x^2 - 3x - 11 = 0
2x2+6x-8 = 72 2x2+6x-8-72 = 0 2x2+6x-80 = 0 (2x-10)(x+8) = 0
If: x+3+6x+9 = 0 then 7x+12 = 0 So: 7x = -12 and x = -12/7
the answer is -3x = 0
x2 + 6x + 9 = 81 x2 + 6x = 72 x2 + 6x - 72 = 0 (x+12)(x-6) = 0 x= -12, 6 (two solutions)
x2+6x-40 = 0 (x+10)(x-4) = 0 x = 4 or x = -10